High-throughput screening of 2D van der Waals crystals with plastic deformability - Zhiqiang Gao; Tian-Ran Wei; Tingting Deng; Pengfei Qiu; Wei Xu; Yuecun Wang; Lidong Chen; Xun Shi (Nature Communications, 2022)
It is still challenging to discover plastically deformable inorganic semiconductors. Here, the authors report a high-throughput screening of tens of potential 2D van der Waals crystals that can deform plastically accompanied with experimental verification.